BlaPSZ-1, a novel AmpC gene identified from a Pantoea isolate - Zhao, Jingxuan; Zhang, Yuan; Sha, Yuning; Lin, Naru; Zhang, Guozhi; Lu, Junwan; Zhu, Tingting; Zhang, Xueya; Li, Qiaoling; Zhang, Hailin; Lin, Xi; Li, Kewei; et al. (Frontiers in Microbiology, 2023)
Background: Pantoea species of the family Erwiniaceae are well-known plant pathogens and animal and human conditional pathogens. Due to the widespread and continuous use of antimicrobials, multidrug-resistant strains continue to emerge, making clinical treatment difficult; therefore, there is an increasing need to clarify the mechanisms of drug resistance. Methods: The rabbit anal fecal sample was collected by a swab and the streak plate method was used to isolate single colonies. The standard agar dilution method was used to determine the minimum inhibitory concentrations (MICs) against antimicrobials. The complete genome sequence of the bacterium was obtained using Next-Generation Sequencing platforms. The potential resistance gene was annotated based on Comprehensive Antibiotic Resistance Database (CARD) and verified by molecular cloning. The β-lactamase PSZ-1 was expressed via pCold I expression vector and its enzyme kinetic parameters were analyzed. The genetic environment and evolutionary process of the novel resistance gene related sequences were analyzed by bioinformatic methods. Results: The isolate Pantoea endophytica X85 showed some degree of resistance to penicillins as well as cephalosporins. A novel AmpC resistance gene designated blaPSZ-1 in this work was identified to be encoded in the plasmid (pPEX85) of P. endophytica X85. BlaPSZ-1 showed resistance to penicillins and several first-, second- and third-generation cephalosporins as well as aztreonam, but it did not show resistance to the fourth-generation cephalosporins or carbapenems tested. Enzyme kinetic assays revealed that it could hydrolyze amoxicillin, penicillin G, cephalothin, and cefazolin, and its hydrolytic activity could be strongly inhibited by the inhibitor avibactam, which was generally consistent with the antimicrobial susceptibility testing results. No hydrolytic activity was observed for third-generation cephalosporins or aztreonam. Conclusion: In this study, a novel AmpC β-lactamase gene designated blaPSZ-1 was characterized and it was encoded in the plasmid of the bacterium P. endophytica X85. It shows resistance to penicillins and several cephalosporins. The discovery of novel drug resistance mechanisms can help guide the scientific use of drugs in animal husbandry and clinical practice, effectively avoiding the abuse of antimicrobials and thus preventing the further development and spread of bacterial resistance.